Gastropod community structure in the water of Terkulai Island Tanjungpinang City - Sahilla, Dilla; Susiana, Susiana; Kurniawan, Dedy; Karyawati, Karyawati; Rochmady, Rochmady (Sangia Research Media and Publishing, 2023)
Gastropods are marine biota found in the waters of Pulau Terkulai, Tanjungpinang City and are one of the catch of fishermen. However, information on the structure of the gastropod community in these waters is not widely known. The purpose of this study was to determine the types of gastropods, gastropod community structure, and the relationship between gastropod community structure and environmental parameters in the waters of Terkulai Island. This research was conducted in April-August 2023. Determination of sampling points using random sampling method as many as 30 points with sampling plots measuring 1x1m2. The results of this study obtained 650 individuals with 15 species of gastropods. The highest density was found in Batillaria attramentaria species with a total of 12.20 ind/m2. Gastropod community structure diversity value (H') ranged from 1.512 which is classified as moderate. The uniformity value (E) ranges from 0.558 which is classified as moderate and the dominance value (D) ranges from 0.353 which is classified as moderate. The results of the measurement of the physicochemical parameters of the waters are still at a feasible threshold for gastropod life. The principal component analysis (PCA) shows that the density with water parameters has a positive correlation with temperature and organic matter.